Thermochemistry and photochemistry of spiroketals derived from indan-2-one: Stepwise processes versus coarctate fragmentations - Bucher, Götz; Heitmann, Gernot; Herges, Rainer (Beilstein Journal of Organic Chemistry, 2013)
Coarctate reactions are defined as reactions that include atoms at which two bonds are made and two bonds are broken simultaneously. In the pursuit of the discovery of new coarctate reactions we investigate the fragmentation reactions of cyclic ketals. Three ketals with different ring sizes derived from indan-2-one were decomposed by photolysis and pyrolysis. Particularly clean is the photolysis of the indan-2-one ketal 1, which gives o-quinodimethane, carbon dioxide and ethylene. The mechanism formally corresponds to a photochemically allowed coarctate fragmentation. Pyrolysis of the five-ring ketal yields a number of products. This is in agreement with the fact that coarctate fragmentation observed upon irradiation would be thermochemically forbidden, although this exclusion principle does not hold for chelotropic reactions. In contrast, fragmentation of the seven-ring ketal 3 is thermochemically allowed and photochemically forbidden. Upon pyrolysis of 3 several products were isolated that could be explained by a coarctate fragmentation. However, the reaction is less clean and stepwise mechanisms may compete.
Keywords: coarctate reaction; fragmentation; matrix isolation; photolysis; pyrolysis; spiroketal